Adaptação do modelo de Streeter - Phelps para modelagem da qualidade da água em uma grande bacia semiárida - Mendes, Wagner José da Silva (2014)
This paper presents an adaptation of the classical model of Streeter-Phelps modeling of Dissolved Oxygen (DO) and Biochemical Oxygen Demand (BOD) in the basin of the Upper Jaguaribe (25,000 km2), State of Ceara, Brazil. The adaptation of the model consisted of the numerical solution of differential equations Streeter-Phelps, considering the effect of incremental flows and sewage releases over the sections, as well as the variability of the sections of rivers and tributaries. For model calibration, including the adjustment of reaeration coefficients (K2) and removal of BOD (Kd), we used the data of the Plan of Management of Waters of the Rio Jaguaribe Basin. Calibration results showed that this simplified model represented well the balance between DO and BOD in a large semi-arid basin, with a good fit for both parameters. For OD, the average deviation was 8.44% and 6.04% by the end and beginning of the rainy season, respectively. As for BOD, the deviations were 18.51% and 30.43% for the two seasons, respectively. In both periods, the OD remained within the standards for Class 2 of Resolution CONAMA 357/2005 throughout the stretch and the BOD breached this limit on a short stretch near the city of Taua. With the already calibrated model were simulated three scenarios: a large full, using as reference flow Q10 of a historical series of Jaguaribe; drought, using the Q50 of the series; and implementation of a WWTP with 80% removal of BOD in all seats. The simulations showed consistent results and that serve as a basis for management of water resources of the study area